Laparoscopic-assisted duhamel for hirschsprung's children older than 3 years - Ahmed Arafa; Haytham Esmat Eltantawi; Moutaz Ragab (Wolters Kluwer Medknow Publications, 2022)
Context: Hirschsprung's disease (HD) is a congenital anomaly affecting the enteric nervous system commonly the rectosigmoid region. Treatment is surgical where the aganglionic segment is resected, and bowel continuity is achieved by a colo-anal anastomosis. In 1999, Georgeson et al. proposed a new technique of primary laparoscopic-assisted pull through for HD as a new gold standard. Aim of the Study: To evaluate the outcome of the laparoscopic Duhamel procedure for the management of HD in children older than 3 years. Methods: This study was performed on 8 patients who were more than 3-year-old, with confirmed diagnoses of HD. Patients who initially presented with enterocolitis or obstruction were excluded from this study. In all cases, laparoscopic-assisted Duhamel was done. Results: We reported our results for the 1st year follow-up period and divided our results into early outcome for the first 3 months postoperative during which we had 2 cases complaining of enterocolitis that responded to conservative treatment, we observed 2 cases of perianal excoriation that responded to medical treatment while the late outcome was reported after 3 months postoperative: We had two cases with attacks of enterocolitis at 6 months and 9 months postoperatively that needed conservative treatment in the hospital in the form of parenteral antibiotics, rectal irrigation, intravenous fluids and NP0. There was neither anastomotic leak nor stenosis. Conclusion: Laparoscopic Duhamel for the management of HD in children older than 3 years is safe and useful procedure.